Graphic Static, Numerical and Experimental Analysis of a Semicircular Masonry Arch (Proceedings of Faculty of Civil Engineering, 2022)
This paper presents the structural analysis of a masonry semicircular arch loaded with a point force at quarter span. The analysis of masonry arch structures is based on the arch geometry instead on its strength. The arch is stable if a thrust line in equilibrium with the external load can be found within the arch geometry. Using the principle of virtual work the limit force at which the arch collapses is determined. The results were finally compared with experimentally obtained results on a timber arch model, where the load was gradually increased until the arch collapsed.
Keywords: masonry structures; semicircular arch; thrust line; collapse mechanisms